2015
DOI: 10.1039/c5tb00280j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of different sized nano-silver loaded on functionalized graphene oxide with highly effective antibacterial properties

Abstract: Graphene oxide (GO) has attracted great interest in many different areas, as a delivery vehicle for antibacterial agents and has shown high potential. Although silver nanoparticles (AgNPs) have strong antibacterial effect, the biological application of AgNPs is often hindered by their aggregation and low stability. In this study, we developed an approach of polyoxyethylene bis (amine) (PEG) directed AgNPs grown on GO, then we combined the two materials to prepare a series of functionalized GO bearing different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(53 citation statements)
references
References 52 publications
1
50
2
Order By: Relevance
“…Before using these silver nanoparticles as antibacterial and antifungal treatment for the protection of straw bales, it is necessary to study the toxicity of these Ag MNPs against human cells. HEK cells are very commonly used for testing the toxicity of metal nanoparticles [23]. Therefore, the cytotoxicity of these Ag MNPs was investigated on HEK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Before using these silver nanoparticles as antibacterial and antifungal treatment for the protection of straw bales, it is necessary to study the toxicity of these Ag MNPs against human cells. HEK cells are very commonly used for testing the toxicity of metal nanoparticles [23]. Therefore, the cytotoxicity of these Ag MNPs was investigated on HEK cells.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicate membrane thickness is critical to nanofiltration performance. Chen et al [29] found a negative correlation between the size of AgNPs in GO@PEG composite membranes and antibacterial activities. However, there are few studies about how the size of AgNPs on GO membranes effects the permeability and rejection of organic dye.…”
Section: Introductionmentioning
confidence: 99%
“…Table exhibits the MIC and the MBC of the chitosan‐CMC silver nanocomposite. The antibacterial activity is affected by release of silver nanoparticles, as well as the size of the nanoparticles and the type of the microorganisms . The MBC/MIC ratio is a parameter that indicates the bactericidal capacity of the silver nanocomposite.…”
Section: Resultsmentioning
confidence: 99%